MILANGKALA DESA SAGULING: KAJIAN SEJARAH LOKAL DALAM KONTEKS PEMBANGUNAN MASYARAKAT CIAMIS - Aan Anwar Sihabudin; Andang Andi (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This discussion examines the history of Saguling Village, an area located in Baregbeg District, Ciamis Regency. This study uses historical methods that include heuristics, verification, interpretation, and historiography. Although the origins of Saguling Village are still not fully revealed, through the search for oral stories and toponymy, a connection was found between this village and the Sunda Galuh Kawali Kingdom in the 15th century AD. The existence of the figure Wangun Denta Kadea, who is a family member of the Sunda Kawali King Prabu Niskala Wastu Kancana, is an important point in the narrative of the formation of Saguling Village. In addition, this article also discusses other historical traces such as hermitages and graves scattered in the Saguling Village area, which add mystical and spiritual dimensions to the history of this village. This study aims to reconstruct the local history of Saguling Village, understand the identity of its people, and reveal cultural heritage that needs to be preserved.